Оцінка виявлених порівняльних переваг експорту туристичних послуг України до ЄС - Почерніна, Наталя Вікторівна; Почернина, Наталья Викторовна; Pochernina, Natalia (My University, 2021)
UK: У статті оцінюється рівень виявлених порівняльних переваг країн Європейського Союзу відносно експорту туристичних послуг України за десятирічний період. Підприємництво у сфері подорожей та туризму є важливим сегментом ринкової економіки багатьох країн світу та чинником інтернаціоналізації господарського життя. У зв’язку із цим здобуття конкурентних переваг у міжнародному туризмі є пріоритетним завданням не лише для суб’єктів мікрорівня, а й для окремо взятих регіонів та країни у цілому. Для формування «дорожньої карти» реалізації даного завдання оцінка сучасних реалій є вихідною передумовою. За рівнем конкурентних переваг на основі індексу Баласса країни ЄС розподілені по групах, для яких визначено пріоритетні напрями туризму. Практичне значення отриманих результатів полягає у можливості їх використання для обґрунтування програм міжнародного співробітництва, а також для розроблення стратегій розвитку туристичної сфери на регіональному та національному рівнях. EN: The revival problem of travel and tourism sphere after the devastating consequences of the pandemic has become very urgent for those countries where tourism is an important source of national income and an activity that creates jobs. Tourism stimulates the development of small and medium-sized businesses, has significant potential for a creative economy, quickly recoups costs, has a significant environmental effect, has a high level of implementation of the principle of social inclusion, including the use of the labor of women and youth. Ukraine in the Development Strategy until 2030 declared the goal of ensuring the development of tourism as one of the drivers of the socio-cultural and economic development of the regions. Important tasks for the implementation of this goal are the quantitative increase in tourist flows and increasing their competitiveness. Assessment of modern realities is the initial prerequisite for the formation of a roadmap for the implementation of these tasks. This is important for both domestic and international tourism. Achieving sustainable competitive advantages in the export of tourism services is a strategic goal of Ukraine. Her commitment to the European vector of development influenced the choice of the object of research. Such an object is the tourist flows from Ukraine to the EU. The subject of the research is the assessment of the comparative advantages of the export of tourist services in Ukraine. The Balassa index for a ten-year period was used in the calculation methodology. The purpose of this article is a comparative analysis of the countries of the European Union in terms of the revealed comparative advantages of the export of tourist services in Ukraine. The obtained results made it possible to distribute the EU countries into groups for which specific directions of stimulating the export of tourist services in Ukraine were determined. The practical significance of the obtained results lies in the possibility of their use to substantiate programs of international cooperation at the regional and national levels, as well as to develop strategies for the development of the tourism sector at the metho and macro levels.
Assessment of the revealed comparative advantages of Ukraine's tourism services export to The Eu
Keywords: міжнародний туризм; конкурентні переваги; порівняльний аналіз; експорт; індекс Баласса; international tourism; competitive advantages; comparative analysis; export; Balassa index